2010
DOI: 10.1007/s12020-010-9345-1
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating hormone regulation of microRNA expression on progesterone production in cultured rat granulosa cells

Abstract: MicroRNAs (miRNAs) regulate gene expression post-transcriptionally by interacting with the 3' untranslated regions of their target mRNAs. Previously, miRNAs have been shown to regulate genes involved in cell growth, apoptosis, and differentiation, but their role in ovarian granulosa cell follicle-stimulating hormone (FSH)-stimulated steroidogenesis is unclear. Here we show that expression of 31 miRNAs is altered during FSH-mediated progesterone secretion of cultured granulosa cells. Specifically, 12 h after FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 42 publications
2
71
1
1
Order By: Relevance
“…Northern blotting analyses confirmed that these represented actual differences in tissue miRNA expression and therefore they are likely to play a role in the regulation of follicular differentiation. Interestingly, four of the nine miRNAs identified as being highly expressed in follicles were previously reported to be upregulated by FSH in rat granulosa cells whereas miR-21, which was expressed at low levels in sheep follicles, was downregulated by FSH (Yao et al 2010b). miRNAs and ovarian follicular differentiation Wang et al 2011), including roles in modulating inflammation, innate immunity and angiogenesis (Chen et al 2004, Otsuka et al 2008, Yamakuchi et al 2008, Liu et al 2009, Guo et al 2010, Jennewein et al 2010, Kuhn et al 2010, Sheedy et al 2010, Caporali et al 2011, Shatseva et al 2011, all of which are intrinsically associated with ovulation and early luteogenesis (Espey & Richards 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Northern blotting analyses confirmed that these represented actual differences in tissue miRNA expression and therefore they are likely to play a role in the regulation of follicular differentiation. Interestingly, four of the nine miRNAs identified as being highly expressed in follicles were previously reported to be upregulated by FSH in rat granulosa cells whereas miR-21, which was expressed at low levels in sheep follicles, was downregulated by FSH (Yao et al 2010b). miRNAs and ovarian follicular differentiation Wang et al 2011), including roles in modulating inflammation, innate immunity and angiogenesis (Chen et al 2004, Otsuka et al 2008, Yamakuchi et al 2008, Liu et al 2009, Guo et al 2010, Jennewein et al 2010, Kuhn et al 2010, Sheedy et al 2010, Caporali et al 2011, Shatseva et al 2011, all of which are intrinsically associated with ovulation and early luteogenesis (Espey & Richards 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, miRNA-145 may not necessarily lead to the modulation of specific predicted functions or targets, but it has been reported to function as a regulator of cell proliferation and as a tumor suppressor (20,69,79,84). A number of studies have attempted to identify and characterize miRNAs in adrenal and gonadal tissues and cells (18,24,45,47,48,50,54,63,68,80,81,83), but information about their potential targets or hormonal regulation is generally lacking except in a few instances. For example, miRNA-378 has been reported to regulate estradiol production in porcine granulosa cells by targeting aromatase (47).…”
Section: Discussionmentioning
confidence: 99%
“…Using H295R human adrenocortical cells, it was shown that miRNA-21 increases aldosterone secretion and cell proliferation, although no specific target for this miRNA was reported (68). Very recently, Yao et al (81) reported that expression of a large number of miRNAs is either upregulated or downregulated in cultured rat granulosa cells in response to FSH stimulation. Surprisingly, the expression of both miRNA-125a-5p and miRNA125b-5p was found to be upregulated in response to 12 h of FSH treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, cAMP did not increase the levels of miR-21 in cultured granulosa cells but miR-21 spontaneously increased within 12 h after plating, a response that was not affected by the presence of serum in culture media (Carletti et al 2010). Similarly, another study reported that treatment of mouse granulosa cells with FSH increased miR-132 levels but not miR-21 (Yao et al 2010b). Consistent with these findings, we found that treatment of cultured bovine granulosa cells with forskolin (an adenylate cyclase agonist) to promote luteinisation was followed by a decrease in the levels of miR-125b and miR-145, as observed during the follicular-luteal transition in vivo (McBride et al 2012); in contrast, levels of miR-21 and miR-34a spontaneously increased in the cultured cells regardless of treatment with forskolin.…”
Section: Involvement Of Mirnas During Ovulation and The Follicular-lumentioning
confidence: 93%